Analisis Penggunaan Smartphone dan Stres dengan Kejadian Insomnia pada Mahasiswa Kesehatan Masyarakat Universitas Jambi - Vinna Rahayu Ningsih; Vivit Sri Rahyuni (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2023)
Health is a very important need for humans, one of the efforts to maintain health, such as adequate rest or sleep and stress management, poor sleep quality is called insomnia, insomnia can have a negative impact on body health, such as the risk of infectious diseases such as high blood pressure and heart disease, Several factors lead to high rates of insomnia. in students in the form of excessive smartphone use and stressful conditions. The purpose of this study was to determine the relationship between smartphone use and stress with the incidence of insomnia among public health students at Jambi University. The research method is an analytic observational study with a quantitative approach using a cross-sectional design with a sampling technique using proportional stratified random sampling as many as 8 respondents. Data analysis with chi-square test. The results of data analysis found that there is a significant relationship. between smartphone use (p = 0000) and stress (p = 0000) on insomnia in public health students at the University of Jambi. The conclusion of the study is that there is a relationship between smartphone use and stress with insomnia in public health students at the University of Jambi.